Pulmonary sarcoidosis. (June 2020) - Butler, Marcus W.; Keane, Michael P.
Abstract: Sarcoidosis can occur after genetically susceptible individuals interact with unidentified environmental antigens. Diagnosis requires clinical evaluation, chest radiography, lung function testing, judicious tissue biopsy (endobronchial ultrasound now being a preferred method) and exclusion of other granulomatous disease. No long-term systemic therapy is usually needed for the common presentation of Löfgren's syndrome (bilateral hilar lymphadenopathy, erythema nodosum, transient iritis). Individuals whose disease needs treatment early after diagnosis have increased mortality risk. Corticosteroids remain first-line therapy, indicated for nearly all patients presenting with new pulmonary infiltrates and worsening lung function, and for those with critical extrathoracic organ dysfunction or hypercalcaemia. Corticosteroid-sparing immunosuppressive agents such as methotrexate, azathioprine or hydroxychloroquine can help minimize drug toxicities. Certain anti-tumour necrosis factor-α agents (infliximab, adalimumab) sometimes have a useful role in refractory disease as a supplement to other therapies, with 18 fluorodeoxyglucose positron emission tomography increasingly useful for assessing refractory disease. Methylphenidate can help sarcoidosis-related fatigue. Pulmonary hypertension can complicate advanced pulmonary sarcoidosis, resulting in sarcoid-related pulmonary vasculopathies, with increased mortality. Treatment options include epoprostenol, sildenafil and bosentan. Lung transplantation is successful in end-stage fibrotic disease, but sarcoid granulomas can reoccur in the allograft, and fungal contamination of fibro-bullous cavities can result in increased postoperative systemic infection.